Do Somatic Mitochondrial DNA Mutations Contribute to Parkinson's Disease? - Joanne Clark; Ying Dai; David K. Simon (Parkinson's Disease)
A great deal of evidence supports a role for mitochondrial dysfunction in the pathogenesis of Parkinson's disease (PD), although the origin of the mitochondrial dysfunction in PD remains unclear. Expression of mitochondrial DNA (mtDNA) from PD patients in “cybrid” cell lines recapitulates the mitochondrial defect, implicating a role for mtDNA mutations, but the specific mutations responsible for the mitochondrial dysfunction in PD have been difficult to identify. Somatic mtDNA point mutations and deletions accumulate with age and reach high levels in substantia nigra (SN) neurons. Mutations in mitochondrial DNA polymerase γ (POLG) that lead to the accumulation of mtDNA mutations are associated with a premature aging phenotype in “mutator” mice, although overt parkinsonism has not been reported in these mice, and with parkinsonism in humans. Together these data support, but do not yet prove, the hypothesis that the accumulation of somatic mtDNA mutations in SN neurons contribute to the pathogenesis of PD.